The Politics of Reproduction Adoption, Abortion, and Surrogacy in the Age of Neoliberalism - Roy, Modhumita; Thompson, Mary (The Ohio State University Press, 2019)
The Politics of Reproduction: Adoption, Abortion and Surrogacy in the Age of Neoliberalism uniquely brings together three sites of reproduction and reproductive politics to demonstrate their entanglement in creating or restricting options for family-making. The original essays in this collection-which draw from a wide range of disciplinary and theoretical perspectives-are attentive to neoliberalism's reshaping of economies and intimacies to better understand the politics of reproduction. By looking at particular instances (surrogacy in Mexico, forced sterilization in Peru, and racialized biopolitics in post-Katrina Mississippi, among other sites), The Politics of Reproduction focuses on the effects of a radically altered economic landscape on individual choice-making. As a whole, the volume critically engages the question of choice to better understand the costs of a political and ideological climate that encourages, even demands, individual solutions to intractable social problems.